2009
DOI: 10.1227/01.neu.0000348550.47441.4b
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Crm1 in Human Gliomas and Its Significance in P27 Expression and Clinical Prognosis

Abstract: The current results showed that CRM1 and p27 expression were associated with glioma grade and that high CRM1 protein expression might be related to poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 26 publications
9
133
0
Order By: Relevance
“…Mechanistically, overexpression of XPO1 enhances export of nuclear tumor suppressor proteins such as p53, BRCA1, allophycocyanin, and NMP1, resulting in drug resistance. 33 Overexpression of XPO1 has also been associated with drug resistance and poor outcome in many solid tumors such as glioblastoma, cervical and ovarian cancer, [35][36][37] and various hematologic malignancies, including myeloma, 38 chronic lymphocytic leukemia, 26 T-cell acute lymphoblastic leukemia, acute myeloid leukemia, [39][40][41] and BCR-ABL1-driven blastic transformation. 19,42 In the shRNA library screen, shRAN-infected cells were depleted by fourfold in K562 R compared with K562 S cells (supplemental Table 4) following 9 days in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, overexpression of XPO1 enhances export of nuclear tumor suppressor proteins such as p53, BRCA1, allophycocyanin, and NMP1, resulting in drug resistance. 33 Overexpression of XPO1 has also been associated with drug resistance and poor outcome in many solid tumors such as glioblastoma, cervical and ovarian cancer, [35][36][37] and various hematologic malignancies, including myeloma, 38 chronic lymphocytic leukemia, 26 T-cell acute lymphoblastic leukemia, acute myeloid leukemia, [39][40][41] and BCR-ABL1-driven blastic transformation. 19,42 In the shRNA library screen, shRAN-infected cells were depleted by fourfold in K562 R compared with K562 S cells (supplemental Table 4) following 9 days in culture.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Thus, XPO1 inhibition may result in increased levels of active TSP, and orally bioavailable selective inhibitors of nuclear export (SINE) that covalently bind and inhibit XPO1 are being explored as a novel therapeutic approach in solid tumors and hematologic malignancies.…”
Section: 3mentioning
confidence: 99%
“…CRM-1 expression has been found to correlate with a more aggressive tumor status and it has been suggested that CRM-1 may have prognostic value in gliomas, osteosarcomas, ovarian cancers and pancreatic cancers (18,20,32,33). Previous studies have also demonstrated an association between CRM-1 expression and resistance to chemotherapy and thus, potent inhibitors of CRM-1 are currently being developed for use in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%